Paediatric pelvic injuries: a retrospective epidemiological study from four level 1 trauma centers - Salášek, Martin; Havránek, Petr; Havlas, Vojtěch; Pavelka, Tomáš; Pešl, Tomáš; Stančák, Andrej; Hendrych, Jan; Džupa, Valér (International orthopaedics, 2021)
AIM OF THE STUDY: Epidemiologic evaluation of pelvic ring injuries in children. METHODS: Retrospective analysis over a period of 13 years, excluding pathological fractures. AO/OTA type, epidemiological data, type of treatment, and complications were recorded. Data were assessed using Fisher's exact test and Wilcoxon test. RESULTS: 243 boys, 115 girls, mean age (SD) 14.1 ± 3.0 years, AO/OTA types: 281 A, 52 B, 25 C. Multiple trauma: 62, combined trauma: 59, mono-trauma: 237. 281 patients were treated non-operatively, 97 surgically. ETIOLOGY: traffic accidents 88, falls from a great height 37, crushing injuries four, and sports injuries 192, simple falls 30, others seven. High-energy mechanisms prevailed in types B and C. Low-energy mechanism in type A (p < 0.0001). Similar differences were found between type A (p = 0.0009) and in case type C requiring surgery and cases treated non-operatively (p < 0.0001). Twenty-six patients (7.3%) had complications (pelvic asymmetry 5, neurological deficits 5, non-union 1, ectopic calcification 4, others 7). Higher complication rates were associated with types B and C (p = 0.0015), with surgically treated cases (p < 0.0001) and multiple trauma (p = 0.0305). DISCUSSION: Results of this trial were comparable with other studies. CONCLUSION: Sports injuries accounted for most type A injuries, while types B and C tended to be associated with high-energy trauma. Complications were associated with the severity of pelvic trauma, more common in surgically treated group of patients; this is primarily linked to the surgical cases being more serious as well as the associated injuries.
Keywords: Male; retrospektivní studie; Trauma Centers; traumatologická centra; Adolescent; polytrauma; Child; dítě; mužské pohlaví; Epidemiology; mladiství; pánevní kosti; lidé; Fracture; ženské pohlaví; Humans; Pelvic ring; Pelvic Bones; Pediatric; Retrospective Studies; Female; fraktury kostí; Multiple Trauma; Fractures, Bone; Multicentric study